I.i.21.i Minutes, - Labour Party (Ireland) (1990)
Minutes of the Administrative Council which took place on 19 Dec 1990 principally concerning: ratification of local election candidates; the Gulf War; and national collection returns. Minutes signed by Mervyn Taylor TD, Party Chair. Also includes: agenda; press release by Dick Spring TD, Party Leader; two copies of speech by Dick Spring TD, Party Leader to the Administrative Council; organisation committee report; finance report; report of the International Secretary; Labour Youth report; and policy document on Party organisation prepared by Labour Left co-operative members of the Administrative Council. (25 pp)